Financial Factors Influencing the Performance of MSMEs in Surabaya - Ninnasi Muttaqiin; Nabilla Lutfi Wahyudi (JURISMA : Jurnal Riset Bisnis & Manajemen, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in driving both macro and microeconomic growth in Indonesia. However, many MSMEs still face obstacles in financial management, limited access to financial services, and low levels of financial literacy, which hinder their performance and sustainability. This study aims to examine the influence of financial literacy, financial inclusion, and financial management on MSME performance in Bulak District, North Surabaya. A quantitative research method was employed, using purposive sampling to collect primary data through questionnaires distributed directly to 95 MSME owners. The data were analyzed using multiple linear regression. The findings reveal that financial literacy, financial inclusion, and financial management each have a significant positive effect on MSME performance. These results suggest that improving financial knowledge, access to financial services, and effective financial management practices can enhance the business performance and growth potential of MSMEs in Bulak District.     Keywords: Financial Literacy; Financial Inclusion; Financial Management; MSME Performance; Personal Finance